Persistence and adherence of solifenacin treatment for Japanese women with overactive bladder - Minoru Kobayashi; Akinori Nukui; Shinsuke Kurokawa; Tatsuo Morita (Urogynaecologia International Journal, 2012)
Persistence and adherence of overactive bladder (OAB) medication have reported to be generally lower in real-world setting as compared with those in clinical trials. However, this information in Japanese population has not been well addressed. Medical records were reviewed for solifenacin as an initial treatment for 172 women with OAB symptom to examine medication persistence, switching, adherence, and the reasons for discontinuation. The associations between persistence and the reasons for discontinuation as well as concomitant conditions regarded as OAB-related risk factors were assessed. The 6-month and 1-year persistence rate of solifenacin were 39.8% and 27.8%, respectively. Consequently, 121 patients (70.3%) discontinued solifenacin, of whom 18 (14.9%) patients switched to other OAB drugs and 9 (7.4%) patients restarted solifenacin. Thus, the adherence rate was 66.8%. More women discontinued solifenacin owing to symptom resolution (41.3%) rather than unfavorable outcomes such as adverse effects (12.4%) and lack of efficacy (21.5%). However, such reason for discontinuation was not the determinant of persistence of solifenacin. There was a non-significant trend towards higher persistence for those with OAB-related risk factors. Japanese women discontinued solofenacin treatment with various reasons in real-world practice, resulting in much lower persistence as compared with clinical trials. A further prospective study in a larger cohort of patients is awaited to better assess their persistence and adherence and understand exact efficacy and tolerability of antimuscarinics for Japanese patients with OAB.